Studi Kompetatif Over Kredit Motor Perspektif Kitab Undang-Undang Hukum Perdata dan Kompilasi Hukum Ekonomi Syariah - Muhammad Muhammad; Abu Bakar; Nur Hakimah (Al-Aqad, 2025)
This study aims to analyze the practice of motorcycle credit transfer (oper kredit motor) among the community in Pontianak City from the perspectives of the Indonesian Civil Code (KUHPerdata) and the Compilation of Sharia Economic Law (KHES). The research employs a juridical-empirical approach. Secondary data sources include books on civil law, Islamic law, literature on credit and banking, journals, theses, dissertations, and relevant websites. Data were collected through observation and documentation, and analyzed qualitatively to draw conclusions. The findings indicate that: 1) The procedure for motorcycle credit transfer is permissible under the Civil Code, provided that the essential elements and conditions of the agreement are fulfilled and mutually agreed upon by the debtor and creditor; 2) Under KHES, such credit transfer is also allowed, as long as it complies with the requirements of hiwalah, including legal capacity (ahliyyah), sound mind, and tamyiz (discernment); 3) Both legal systems share similarities in requiring the parties involved in the contract—muhiil (the original debtor), muhal (the creditor), and muhal ‘alaih (the new debtor)—to be legally competent, mentally sound, and to express a valid offer and acceptance (ijab-qabul). The main difference lies in the age requirement for legal capacity: the Civil Code sets it at 21 years, whereas KHES recognizes legal capacity from the age of 18.